Mandates and the Affordability of Health Care - Sherry Glied (SAGE Publishing, 2009)
This paper examines the economic rationale of affordability exemptions in the context of a health insurance mandate. I provide an economic definition of affordability and discuss how it is implemented in the contexts of food, housing, and health care. Affordability standards are frequently used in making food and housing policy, but both empirically and theoretically health care operates quite differently than these other merit goods. This helps explain why the use of affordability in health policymaking is so different from its use in these other contexts. I conclude with some suggestions about how to improve affordability exemption rules in health policymaking.